Expressive writing in a Saudi university English foreign language (EFL) classroom: Evaluating gains in syntactic complexity [version 1; peer review: 2 approved] - Shatha Ahmed Abdulaziz Alkhalaf (F1000Research, 2022)
Background: This study determines if the English foreign language (EFL) Saudi students achieve greater syntactic complexity when they engage in expressive writing than when they write about a general topic. Methods: This study employs an ex post facto research design to compare the writing output of EFL learners. The sample comprised of 24 college students enrolled in an English writing course, at Department of English and Translation, College of Sciences and Arts, Qassim University, Saudi Arabia for the academic year 2021-2022. The participants were assigned randomly, and their writing was analyzed using the computer software named Web-based L2 Syntactic Complexity Analyzer. Lu’s (2010) four board element of syntactic complexity and 14 units is employed to analyze the data. Results: Results show that students achieve higher syntactic complexity when engaging in writing on emotional topics (expressive writing) than when writing on general topics. Further, analysis shows that students' emotional writings are significant on three syntactic complexity measures, i.e., length of production units; amount of subordination; and phrase sophistication. The fourth measure, i.e., coordination, does not reflect significant differences between their expressive writing and general writing. Conclusions: The study's implications are expected to aid EFL instructors and curriculum designers in successfully implementing language education, particularly in writing, in the Saudi context. In line with the input hypothesis, this research suggests that writing about personal emotional events may enhance the quality of language two (L2) writing by increasing syntactic complexity. In this dimension, this study could be additional evidence of the Krashen hypothesis.